2010
DOI: 10.1136/emj.2009.074054
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care pathway for self-harm: our way forward

Abstract: This integrated care pathway (ICP) is evidence of true multidisciplinary working resulting in mutually beneficial outcomes for both the acute and mental health trusts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Suggested risk markers for inclusion in a psychosocial assessment include: mental illness symptoms (particularly depressive symptoms) (Häfner et al . 2010; Priest et al 2008), suicide-related factors (Kripalani et al 2010), violence (Kavanaugh et al 2009), self-neglect (Campayo et al 2009), personal psychosocial problems (National Institute for Health and Clinical Excellence, 2004) and adverse life-styles such as smoking in schizophrenia (Brown et al 2000). A considerable body of research has investigated whether risk assessment can effectively prevent specific adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested risk markers for inclusion in a psychosocial assessment include: mental illness symptoms (particularly depressive symptoms) (Häfner et al . 2010; Priest et al 2008), suicide-related factors (Kripalani et al 2010), violence (Kavanaugh et al 2009), self-neglect (Campayo et al 2009), personal psychosocial problems (National Institute for Health and Clinical Excellence, 2004) and adverse life-styles such as smoking in schizophrenia (Brown et al 2000). A considerable body of research has investigated whether risk assessment can effectively prevent specific adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A full assessment of psychosocial stressors by healthcare professionals is therefore strongly and routinely encouraged to improve patient care (Department of Health and Social Security, 1984; National Institute for Health and Clinical Excellence, 2004). A large number of characteristics of individuals and their environment are believed to be relevant for inclusion in such assessments, including symptoms of mental disorders (particularly depressive symptoms) (Priest et al 2008; Häfner et al 2010), and known risk factors for suicide (Kripalani et al 2010), violence (Kavanaugh et al 2009) and self-neglect (Campayo et al 2009), as well as personal psychosocial problems (National Institute for Health and Clinical Excellence, 2004), physical disorders or adverse life-styles such as smoking in schizophrenia (Brown et al 2000). Mental disorders such as depression, bipolar disorder and schizophrenia are associated with substantial and persisting excess mortality risk (Brown et al 2000; Mykletun et al 2009; Schoevers et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…21 This type of resource utilisation has previously been reported as being an important contributor to appropriate care following self-harm, with integrated care pathways and short-term medical admission resulting in increased psychosocial assessments, decreased medical complications, shorter length of stay and cost savings. 17,35 Future research could consider the reasons underlying hospital admission policies, for example if an individual is admitted because of a psychosocial assessment not being possible at the time of presentation, or where a decision regarding in-patient admission or transfer to another hospital for specialist care cannot be made, because of limited resources at the time of presentation. This may explain the lower rate of psychiatric admissions in hospitals with high conversion rates.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, numerous studies have been conducted with six-month and one-year follow-ups of patients who have been referred to hospitals with intentional poisoning or self-harm. Modifying this scale (expressing it as MSPS) indicated that attempts to committing suicide within 6 months or one year were more frequent in patients with an MSPS score of ˃5 [32]. In addition, other studies stated the cut-off points obtained from this modified scale equal to ˃6, with a sensitivity and specificity of 100% and 68.5% [33], and scores of ˃9 with a sensitivity of 31.3% and a specificity of 94.4% [17].…”
Section: Discussionmentioning
confidence: 99%